#### Answer

$\color{blue}{x^2+6x+9}$

#### Work Step by Step

RECALL:
$(a+b)^2=a^2+2ab+b^2$
Use the formulal above to obtain:
$(3+x)^2
\\=3^2+2(3)(x)+x^2
\\=9+6x+x^2
\\=\color{blue}{x^2+6x+9}$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$\color{blue}{x^2+6x+9}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.